Crystallising whiteness: engaging white students' whiteness through Civil Dialogue®. Issue 1 (2nd January 2020) - Razzante, Robert J.
ABSTRACT: As an interdisciplinary field of study, Whiteness Studies have examined rhetorical strategies that reinforce whiteness ideology and White privilege at both macro- and micro-levels. The current study adds to Whiteness Studies literature by demonstrating various performances of whiteness ideology by White people. In using dominant group theory as a theoretical framework and analytic lens, I demonstrate how Whites reinforce, impede, and dismantle whiteness ideology. That is, rather than exclusively seeking reinforcements of whiteness ideology, dominant group theory also provides a framework to understand ways one can challenge and disrupt the oppressive ideology. Such an approach engages crystallising to demonstrate various performances of whiteness. The study has implications for future research and pedagogy when teaching Whiteness Studies to White students and their various levels of readiness for grappling with their own whiteness.